2021
DOI: 10.1021/acschemneuro.1c00634
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Mouse Cortical Glutamate Uptake Can Be Unveiled In Vivo by a Two-in-One Quantitative Microdialysis

Abstract: Extracellular glutamate levels are maintained low by efficient transporters, whose dysfunction can cause neuronal hyperexcitability, excitotoxicity, and neurological disease. While many methods estimate glutamate uptake in vitro/ex vivo, a limited number of techniques address glutamate transport in vivo. Here, we used in vivo microdialysis in a two-in-one approach combining reverse dialysis of isotopic glutamate to measure uptake ability and zero-flow (ZF) methods to quantify extracellular glutamate levels. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The ratio between the two radio-labelled molecules increased during the wash-out period, peaking 4–6 min after the end of isotopic infusion ( Figure 1 B). Lower glutamate/mannose ratios were found in DMSXL animals, when compared with WT controls, suggestive of defective glutamate uptake ability in the hippocampus, as previously shown in the frontal cortex, another brain region very relevant for DM1 neuropsychological manifestations [ 30 ]. To confirm that the DMSXL traces were indicative of decreased glutamate uptake in the hippocampus, we administered an uptake blocker (dihydrokainate, DHK) concomitantly with the two radio-labelled molecules and measured the glutamate/mannose ratio during the perfusion and wash-out periods.…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…The ratio between the two radio-labelled molecules increased during the wash-out period, peaking 4–6 min after the end of isotopic infusion ( Figure 1 B). Lower glutamate/mannose ratios were found in DMSXL animals, when compared with WT controls, suggestive of defective glutamate uptake ability in the hippocampus, as previously shown in the frontal cortex, another brain region very relevant for DM1 neuropsychological manifestations [ 30 ]. To confirm that the DMSXL traces were indicative of decreased glutamate uptake in the hippocampus, we administered an uptake blocker (dihydrokainate, DHK) concomitantly with the two radio-labelled molecules and measured the glutamate/mannose ratio during the perfusion and wash-out periods.…”
Section: Resultssupporting
confidence: 53%
“…As expected, the unspecific blockade of the glial transporters by DHK decreased the wash-out glutamate/mannose ratio in WT mice to levels that were undistinguishable from those found in the DMSXL hippocampus ( Figure 1 B). We used the area under the curve (AUC) during the wash-out period as an estimate of glutamate uptake ability in the different mouse groups [ 30 ] and confirmed that glutamate uptake was significantly reduced in the DMSXL hippocampus relative to WT controls ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations